Sistem Kendali On/Off Circuit Breaker 150 kV AD20 Tipe 8DN2 di PT. Krakatau Daya Listrik - Endi - Permata; Dimas Aditama (Energi & Kelistrikan, 2020)
In the transmission and distribution system at PT. Krakatau Daya Listrik there is a security system created. In this case Circuit Breaker (CB), which is a security installation of the electricity network. CB that is used is GIS (Gas Insulated Switchgear) type where CB uses SF6 gas (Sulfurhexaflouride) as an insulating medium to extinguish the arc. This research itself aims to understand how the 150 kV GIS AD20 On / Off Circuit Breaker process control system at PT. Krakatau Daya Listrik and how the work processes, instrumentation, advantages and disadvantages and maintenance of the 150 kV GIS AD20 Circuit Breaker at PT. Krakatau Electric Power. Using research methods directly in the field with interviews and analysis. The results of this study are in the form of an understanding of CB operating systems that can be turned on both locally and via remote control and also the results of routine CB maintenance as an indication of the appropriateness of the equipment for operation so that from the associated analysis can be known the strengths and weaknesses of the device, especially the circuit breaker type GIS.